z=xm+n-p
We need to isolate x to one side I will do that on the left side so it looks cleaner, therefore I will first flip the equation.
xm+n-p=z
Now move the n and p to the right side
xm=z-n+p
x=(z-n+p)/m
Hope this helped, if you have any questions about this just comment and I will come answer.
Answer:
90°
Step-by-step explanation:
Answer:
Ray
Step-by-step explanation:
<u>Answer:</u>
First car: 35 gallons
Second car: 15 gallons
<u>Step-by-step explanation:</u>
Assuming
to be the gas consumed by 1st car and
to be the gas consumed by 2nd car.
We know that:
Distance traveled = fuel efficiency × gas consumed
![20x+35(50-x)=1225](https://tex.z-dn.net/?f=20x%2B35%2850-x%29%3D1225)
![20x+1750-35x=1225](https://tex.z-dn.net/?f=20x%2B1750-35x%3D1225)
![35x-20x=1750-1225](https://tex.z-dn.net/?f=35x-20x%3D1750-1225)
![15x=525](https://tex.z-dn.net/?f=15x%3D525)
![x=35](https://tex.z-dn.net/?f=x%3D35)
So
Therefore, first car consumed 35 gallons while second car consumed 15 gallons.